Review of Early Postoperative Metrics for Children Undergoing Resection of Congenital Pulmonary Airway Malformations and Report of Pleuropulmonary Blastoma at a Single Institution - Vandewalle, Robert J.; Easton, Joseph C.; Burns, R. Cartland; Gray, Brian W.; Rescorla, Frederick J. (European Journal of Pediatric Surgery, 2019)
Purpose The purpose of this study is to describe a single institution's 11-year experience treating children with congenital pulmonary airway malformations (CPAMs) and pleuropulmonary blastoma (PPB).Materials and Methods An institutional database was sampled for all patients aged 0 to 18 years from January 1, 2005, to December 31, 2015. Patients with a pathologic diagnosis of CPAM or PPB during this period were reviewed.Results A total of 51 patients with a pathologic diagnosis of CPAM (n = 45; 88.2%) or PPB (n = 6; 11.8%) underwent surgical resection. Among patients treated for PPB, one death occurred approximately 13 months after diagnosis. Although four patients with PPB (four out of six; 66.7%) had radiographic indicators highly suggestive of malignancy prior to surgery, two had a preoperative diagnosis of CPAM (two out of six; 33.3%). Twenty-four patients (24 out of 45; 53.3%) with CPAM underwent resection after developing symptoms and 21 (21 out of 45; 46.7%) were symptomatic at the time of surgery. Mann–Whitney's tests revealed a statistically significant difference in postoperative length of stay (median: 6 vs. 3 days; p < 0.001) and days with thoracostomy tube in place (median 3 vs. 2 days; p = 0.003) for symptomatic versus asymptomatic patients, respectively.Conclusion CPAM patients appear to recover faster from surgery, if performed before the onset of symptoms. There may be a benefit to waiting until at least 3 months of age to complete resection in the asymptomatic patient. A low threshold for resection should be maintained in patients where delineating CPAM from PPB is difficult.
Keywords: congenital pulmonary airway malformation; pleuropulmonary blastoma; surgery